1989
DOI: 10.1246/bcsj.62.4066
|View full text |Cite
|
Sign up to set email alerts
|

A New Preparative Method of 4-Hydroxybenzofuran-2-carboxylic Acid Derivatives

Abstract: 4-Oxo-4,5,6,7-tetrahydrobenzofuran-2-carboxylic acid was prepared from 1,3-cyclohexanedione and ethyl bromopyruvate. Dehydrogenation of this acid or its methyl ester gave 4-hydroxybenzofuran-2-carboxylic acid derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Iodine-methanol reaction mixture has established itself to be more effective than metal–catalyzed aromatization of substituted cyclohexenones to the corresponding phenols or phenol ethers [ 74 , 75 , 76 , 77 , 78 ]. This reagent mixture was also found to be superior to the use of DDQ in dioxane, which was previously employed to dehydrogenate 5-acetyl-4-oxo-4,5,6,7-tetrahydrobenzofuran and methyl-4-oxo-4,5,6,7-tetrahydrobenzofuran-5-carboxylate [ 78 ].…”
Section: Combined Electrophilic and Oxidative Properties Of Iodinementioning
confidence: 99%
“…Iodine-methanol reaction mixture has established itself to be more effective than metal–catalyzed aromatization of substituted cyclohexenones to the corresponding phenols or phenol ethers [ 74 , 75 , 76 , 77 , 78 ]. This reagent mixture was also found to be superior to the use of DDQ in dioxane, which was previously employed to dehydrogenate 5-acetyl-4-oxo-4,5,6,7-tetrahydrobenzofuran and methyl-4-oxo-4,5,6,7-tetrahydrobenzofuran-5-carboxylate [ 78 ].…”
Section: Combined Electrophilic and Oxidative Properties Of Iodinementioning
confidence: 99%
“…Iodine represents a relatively less expensive reagent for oxidative aromatization of cyclohexenone moiety than metal–catalyzed aromatization of substituted cyclohexenones to the corresponding phenol ethers or phenols [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. It is also superior to the use of 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) in dioxane, which was previously employed to dehydrogenate 5-acetyl-4-oxo-4,5,6,7-tetrahydrobenzofuran and methyl-4-oxo-4,5,6,7-tetrahydrobenzofuran-5-carboxylate [ 33 ].…”
Section: Iodine As An Oxidantmentioning
confidence: 99%
“…This reaction, which is believed to proceed by halogenation of the homoannular enol form of the conjugated carbonyl group, was found to occur with conservation of ring junction stereochemistry and without halogenation α to the nonconjugated carbonyl group. Dehydrogenation of 4-oxo-4,5,6,7-tetrahydrobenzofuran-2-carboxylic acid and its methyl ester derivative with copper(II) bromide (CuBr 2 ) in refluxing methanol also afforded the corresponding 4-hydroxy-2,3-dihydrobenzofuran-2-carboxylic acid derivatives [ 4 ]. Despite the observed trans-esterification or esterification, the application of CuBr 2 was found to be more effective than the use of sulfur at 250 ºC or 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) in benzene under reflux [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has also been reported that under similar reaction conditions, the chemoselectivity is reversed. More specifically, β‐dicarbonyl compounds first undergo alkylation with α‐halogenated ketones (Scheme , path b), to yield tricarbonyl compounds V which finally generate furans or pyrroles through Paal–Knorr synthesis , . As far as we know, except for α‐haloketo esters,[9f] intermediates of the so‐called Feist–Bénary synthesis have seldom been separated or characterized, thus causing confusion when it comes to the structure determination of final furan products derived in this fashion.…”
Section: Introductionmentioning
confidence: 99%